From Trend Exposure to Identity Construction: FOMO and Generation Z’s Fashion Consumption on TikTok Shop - Siti Alfia; Desi Erawati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: Fear of Missing Out (FOMO) has become a prominent phenomenon among Generation Z, particularly in fashion consumption through TikTok Shop. Previous studies have primarily examined the relationship between FOMO and consumer behavior quantitatively, while limited research has explored how FOMO shapes consumer lifestyles through subjective experiences in digital environments. Therefore, this study aims to analyze the role of FOMO in the formation of Generation Z’s consumer lifestyle in fashion consumption on TikTok Shop. Research Methods: This study employed a qualitative field research approach involving 15 Generation Z university students at Universitas Islam Negeri Palangka Raya who actively use TikTok and have purchased fashion products through TikTok Shop. Data were collected through semi-structured interviews, observation, and documentation, and analyzed using inductive descriptive analysis. Results: The findings indicate that FOMO emerges through repeated exposure to viral fashion content, social comparison with peers and influencers, and concerns about being left behind in trends. These experiences encourage impulsive purchasing decisions and normalize online shopping habits. Fashion consumption is increasingly driven by the desire for social recognition, self-expression, and digital identity construction rather than functional needs alone. Conclusion: FOMO plays a significant role in shaping the consumer lifestyle of Generation Z on TikTok Shop. Fashion consumption functions not only as an economic activity but also as a means of gaining social recognition and maintaining relevance in digital communities. These findings highlight the importance of strengthening digital and financial literacy to encourage more rational consumption behavior among Generation Z.